(untitled) (Advancements in Homeopathic Research, 2024)
The burden of diabetes is high and increasing globally, and in developing economies like India, mainly fueled by the increasing prevalence of overweight/ obesity and unhealthy lifestyles. In 2019, India had an estimated 77 million people with diabetes, and projections suggest this number will surpass 134 million by 2045. Around 57% of these individuals are currently undiagnosed. The majority of diabetes cases in India are Type 2, and this form of diabetes can result in various complications affecting multiple organs. These complications are broadly categorized into microvascular and macrovascular complications. These complications are a significant cause for increased premature morbidity and mortality among individuals with diabetes, leading to reduced life expectancy and financial and other costs of diabetes leading to profound economic burden on the Indian health care system. It is noteworthy that certain lesser known homeopathic remedies demonstrate efficacy in reducing blood sugar levels, thereby playing a crucial role in the prevention and management of complications associated with diabetes mellitus.